Sistem Informasi Inventaris Barang Sekolah SMK Swasta Pabaku Stabat - Surizar Rahmi Danur; Calvin Pratama; Raheliya Br Ginting (Forum Kerja Sama Penddikan Tinggi (FKPT), 2022)
Inventories of school goods are state-owned goods, either purchased or obtained through government funds on the basis of the imposition of taxes (DPP) or obtained as exchanges or grants as well as making their own to support the smooth teaching and learning process. PABAKU Stabat Vocational School is one of the Educational Institutions in the Stabat area that has an inventory of school goods, the principal is responsible for all access that occurs in schools regarding school inventory items. At SMK PABAKU Stabat, the processing of school inventory items is still done manually by recording books and stored in archive form. This manual recording and storage of data allows for errors in the process of recording goods data, such as; data loss, repeated logging, data retrieval that requires a longer time span. In overcoming this, the author wants to assist employees in making reports through an inventory information system that has been computerized and connected to the internet using the My SQL database.